O religii starożytnych Germanów. Komentarze do księgi VII Geografii Strabona - Kowalski , Andrzej Piotr (Collectanea Philologica, 2023)
In book VII of Strabo’s Geography there are passages about the religion of the ancient Germans. One of them mentions the name of the Chatti priest Libes. In two others, the customs of the Kimbrians are mentioned. The purpose of this article is to interpret the religious customs of these peoples, on the basis of which Strabo’s texts are created. In addition to historical data, linguistic and ethnological materials will be used in a comparative approach. A hypothesis will be presented that the considered texts of Strabo describe the Germanic religion subjected to strong Celtic inﬂuences. The following conditions were considered. In describing the religion of the Kimbrians, Strabo did not have to use Posidonius regarding them as Celts. Such an assumption results from the analysis of texts. Blood divination rituals are known to be a Celtic tradition, but they were performed by Druids. Among the Kimbrians, gray-haired soothsayers did it. The Gauls did not have women – priestesses. Meanwhile, among the Germans, women dealing in divination played an important role. The Germanic element in the activities of the Kimbrians is also the use of ritual stairs, which Strabo writes about. Archaeological and linguistic research proves the great inﬂuence of the Celts on the Germans. Probably Strabo, writing about the Kimbrians as a Germanic tribe, testiﬁed to such a process. Regardless of the ethnic identity of the Kimbrians, the picture of their customs given by Strabo is an important source for research on the religion of the Barbaricum peoples.